Emerging Frontiers in Cardiovascular Diagnostics: A State-of-the-Art Review - Ramadhan, Roy Novri; Sari, Dewi Ratna; Akram, Muh; Nurdiansyah, Farhan (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2023)
Background: The cardiovascular diagnostic landscape is rapidly evolving, with novel and advanced techniques and technologies continually emerging. Detection, monitoring, and management of cardiovascular diseases (CVDs) are quickly changing, which are leading mortality cause globally. Objective:This review aims to provide a comprehensive and up-to-date assessment of the current cardiovascular diagnostic modalities. It seeks to elucidate novel and promising technologies, address their advantages, limitations, and potential integration into clinical practice. Methods: This literature review discusses the recent cardiovascular diagnostics which were obtained from various sources such as PubMed, EMBASE, and Web of Science for articles published in the last decade. Results: The review identified vital emerging frontiers in cardiovascular diagnosis, including advancements in multi-modal imaging (such as PET-MRI), novel biomarkers, artificial intelligence applications, and the growing utility of wearable and remote monitoring technologies. Conclusion: Emerging techniques integration inroutine clinical practice requires careful consideration of their advantages and potential for improving patient outcomes. The review highlights the pressing need for continued research and guideline to ensure these innovations realize their full potential for the future of cardiovascular medicine.